(untitled) (Journal of Environmental Science and Natural Resources, 2016)
This review article presents the updated informationof freshwater Invasive Alien Species (IAS) of fishes of the continents to understand the homogenate progression in global freshwater ecosystems and the leading pathways of freshwater IAS fish introduction throughout the continents. North America contains 45 freshwater invasive fish species within 18 families, which is the most profuse off all other continents, whereas, Australia possesses the lowermost amount of freshwater IAS fish, 18 species under 8 families. Besides, Asia retains 41 freshwater IAS fish under 14 families and Europe acquires 32 species under 18 families. The uppermost spreader IAS fish family is Cyprinidae followed by Cichlidae subsequently. Nine common fishes (Carassius auratus, Cyprinus carpio, Onchorynchus mykiss, Oreochromis mossambicus, Poecilia reticulata, Salmo salar, Salmo trutta and Salvelinusfontinalis) turned out invasive in all the continents (without Antarctica). Among IAS introduction pathways, aquaculture causes the highest percentage of freshwater IAS introduction in all continents. Aquaculture root 25% of IAS fish introduction in Africa, 21% in Asia, 19% in Australia, 20% in Europe, 19% in North America and 19% in South America. There is hardly any documentation on freshwater IAS fishes of Antarctica. Therefore, future research consideration may be designed. J. Environ. Sci. & Natural Resources, 8(2): 63-74 2015